MORALE AMONG FRENCH COLONIAL TROOPS ON THE WESTERN FRONT DURING WORLD WAR I: 1914–1918 - Dean, William (Scientia Militaria - South African Journal of Military Studies, 2011)
The traditional images of the French Army in World War I on the Western Front from Cyril Falls’s to Marc Ferro’s surveys (both entitled The Great War 1914– 1918) have been that of the grizzled yet determined French peasant or worker – the poilu. It is clear from recent research that this is far from accurate and that the French forces were far more heterogeneous than portrayed by previous images.1 Men were called from all over the French empire to serve in the frontline and in logistics units. Virtually every part of the French Empire responded, although somewhat grudgingly, even including Tahiti, which provided a Bataillon Pacifique. Bringing men to a foreign land and culture to fight in a new type of horrific war was quite a strain on these 600 000 soldiers.2 The bulk of these soldiers were drawn from North and West Africa, with smaller numbers coming from Madagascar, Indochina and Equatorial Africa. This article is an attempt at giving an impressionistic glimpse of this subject describing colonial morale both at the frontlines and behind the lines, seeing how they compare to their metropole comrades and trying to gain an understanding of the vie quotiedienne of the colonial soldier.